Self-reflection Levels in Learning among the Medical Students at Faculty of Medicine, Universitas Swadaya Gunung Jati, Cirebon, Indonesia - Faturrahman, Farhan Raka; Permatasari, Tissa Octavira; Meidianawaty, Vivi (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2024)
Background: Self-reflection is one of the most important characteristics that students, especially medical students, need to have during their studies. With the challenges across medical doctor programs, students need to have adequate self-assessment skills. Aims: This study aims to determine the level of self-reflection skills in students of the Faculty of Medicine, Universitas Swadaya Gunung Jati at the academic and professional stages. Methods: This is a descriptive observation research with 418 respondents consisting of students at the academic and professional stages. This study used a reflection-in-learning questionnaire that has been adapted into Indonesian to assess the level of student self-reflection with the results are divided into six levels of indicators: